On the Complete Solution of the Linear Cournot Oligopoly Model - Gehrig, Wilhelm (Review of Economic Studies, 1981)
Journal Article On the Complete Solution of the Linear Cournot Oligopoly Model Get access Wilhelm Gehrig Wilhelm Gehrig Universität Karlsruhe Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 4, October 1981, Pages 667–670, https://doi.org/10.2307/2297208 Published: 01 October 1981 Article history Received: 01 March 1981 Accepted: 01 June 1981 Published: 01 October 1981